Les cinémas arabes en tournée et en tournage festivalier - Gemma Ventura-Mustienes (Revue des Mondes Musulmans et de la Méditerranée)
Over the past two decades, Arab film festivals have proliferated all around the world, inside and outside the borders of the Arab world. Their purpose and actions are complex. On the one hand, they endeavor to introduce Arab films and, with them, the societies which they portray and within which they are made. On the other hand, they have an effect on the image of the Arab culture constructed by the receiving societies, and, in turn on the film creations themselves. To shed light on the subject, we studied a sample selected according to longevity and geographical situations: the festivals we selected have been in existence for at least five years or have been created since 2009 on all continents. We focused our study on the mission and format of these festivals’ first year editions, thereby connecting these cinematographic events to the political, social and cultural contexts in which they take place.